Biological control of Verticillium wilt of olive by Paenibacillus alvei, strain K165 - Emmanouil A. Markakis; Sotirios E. Tjamos; Polymnia P. Antoniou; Epameinondas J. Paplomatas; Eleftherios C. Tjamos (BioControl, 2016)

Symptom development, pathogen isolation and Real-Time QPCR quantification as factors for evaluating the resistance of olive cultivars to Verticillium pathotypes - Emmanouil A. Markakis; Sotirios E. Tjamos; Polymnia P. Antoniou; Epaminondas J. Paplomatas; Eleftherios C. Tjamos (European Journal of Plant Pathology, 2009)

Novel methodologies in screening and selecting olive varieties and root-stocks for resistance to Verticillium dahliae - Polymnia P. Antoniou; Emmanouil A. Markakis; Sotirios E. Tjamos; Epaminondas J. Paplomatas; Eleftherios C. Tjamos (European Journal of Plant Pathology, 2008)

The distribution of ground spiders (Araneae, Gnaphosidae) along the altitudinal gradient of Crete, Greece: species richness, activity and altitudinal range - M. Chatzaki; P. Lymberakis; G. Markakis; M. Mylonas (Journal of Biogeography, 2005)
Aim To study the altitudinal variation of ground spiders (Araneae, Gnaphosidae) of Crete, Greece, as far as species composition, species richness, activity and range of distribution are concerned. Location Altitudinal zones (0–2400 m) along the three main mountain massifs of the island of Crete. Methods Thirty‐three sampling sites were located from 0 to 2400 m a.s.l. on Crete, and sampled using pitfall traps. Material from the high‐activity period of Gnaphosidae (mid‐spring to mid‐autumn) was analysed. Sampling sites were divided into five altitudinal zones of 500 m each. Statistical analysis involved univariate statistics ( anova ) and multivariate statistics, such as multidimensional scaling (MDS) and cluster analysis (UPGMA) using binomial data of species presence or absence. Results Species richness declines with altitude and follows a hump‐shaped pattern. The activity pattern of the family, as a whole, is not correlated with altitude and is highly species‐specific. In the highest zone, both species richness and activity decline dramatically. The altitudinal range of species distribution increases with altitude. On the Cretan summits live highly tolerant lowland species and isolated residents of the high mountains of Crete. Two different patterns of community structure are recorded. Main conclusions Communities of Gnaphosidae on Crete present two distinct structures following the altitudinal gradient, these being separated by a transitional zone between 1600 and 2000 m. This study supports previous results which show a hump‐shaped decline in species richness of Gnaphosidae along altitudinal gradients, leading to a peak at 400–700 m, where an optimum of environmental factors exists. This makes this zone the meeting point of the often opportunistic lowland species with the older and most permanent residents of the island. Rapoport's rule on the positive correlation of the altitudinal range of species distributions with altitude is also supported. The high activity recorded for the species that persist on the high mountains of Crete is indicative of a tolerant arachnofauna, and is considered to result from relaxation of competitive interactions with other species. This is related to a reduction in species numbers, shortening of the activity period on high mountains and the unique presence of high mountain species that thrive only there. As shown in our study, strategies to cope with altitude are species‐specific. Therefore, there cannot exist one single model to describe how animals react to the change in altitude, even under the same environmental conditions.

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Estimation of potato protein content by dye binding - M. S. Kaldy; W. Malewski; P. Markakis (American Journal of Potato Research, 1972)